Low Value Translations and Retellings from Intermediate Languages of Andersen’s Fairy Tale “Thumbelina” - Šelekaitė, Ieva; Kudirka, Robertas (Vertimo studijos, 2022)
Hans Christian Andersen is one of the most famous Danish writers whose fairy tales have been read by almost every child. The first book of Andersen’s fairy tales appeared in Lithuanian in 1895 and their popularity has not faded ever since. However, most Lithuanian translations consist of fairy tales translated not from Danish, but from intermediate languages (English, Spanish, Italian, French). This article analyses abridged, retold versions and translations from the intermediate languages of Andersen’s tale “Thumbelina”. It is concluded that, due to commercialization and the desire to publish the tales more cheaply, they are distorted and simplified. As a result, the storyline changes and the artistically motivated, integral structural elements of content and form are violated.